1991
DOI: 10.1021/bi00230a016
|View full text |Cite
|
Sign up to set email alerts
|

Deamidation of soluble CD4 at asparagine-52 results in reduced binding capacity for the HIV-1 envelope glycoprotein gp120

Abstract: High-performance cation-exchange chromatography of recombinant soluble CD4 (rCD4) allowed the resolution of four charge variants. This charge heterogeneity could be eliminated by neuraminidase treatment of rCD4 and therefore can be attributed to different degrees of sialylation of the carbohydrate portion of this glycoprotein. A single acidic variant was observed upon cation-exchange chromatography of neuraminidase-treated rCD4 that had been stored in liquid solution, pH 7.2, at 25 degrees C for 6 months. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 34 publications
0
27
1
Order By: Relevance
“…A follow-on study that defines the identity and extent of post-translational modifications for amino acids in rPA by LC/MS/MS will be described separately (Powell et al, in preparation). A reduction or complete loss of in vitro or in vivo biological activities has been reported for a variety of deamidated proteins [27,28], while others appear unaffected [29]. It is therefore important to establish methods for evaluating the effects of deamidation on the biological activities and antigenicities of vaccine candidate polypeptides.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-on study that defines the identity and extent of post-translational modifications for amino acids in rPA by LC/MS/MS will be described separately (Powell et al, in preparation). A reduction or complete loss of in vitro or in vivo biological activities has been reported for a variety of deamidated proteins [27,28], while others appear unaffected [29]. It is therefore important to establish methods for evaluating the effects of deamidation on the biological activities and antigenicities of vaccine candidate polypeptides.…”
Section: Discussionmentioning
confidence: 99%
“…At higher levels of AEP, additional Asn residues in TTCF are targeted. 2 Peptides generated from cleavage by AEP at these minor sites were more prevalent in a digest of TTCF37, providing further evidence that aging TTCF perturbed the normal pattern of proteolytic degradation.…”
Section: Resultsmentioning
confidence: 90%
“…For example, a recent study demonstrated that the DNA-damaging antineoplastic drug cisplatin induced the deamidation of two asparagine residues in a flexible loop of the antiapoptotic protein Bcl-xL, preventing its interaction with other proapoptotic Bcl family members and thereby inducing apoptosis (1). Other studies document the deleterious effects of asparagine deamidation on the CD4 binding activity of human immunodeficiency virus gp120 (2), the co-mitogenic and receptor binding activity of murine IL1-␀ 1 (3), and the angiogenic activity of angiogenin (4). Immune recognition of proteins and peptides can also be affected by deamidation/isomerization of asparagine and glutamine residues.…”
mentioning
confidence: 99%
“…Isoaspartyl (iso-Asp) 3 post-translational protein modification occurs at physiological temperatures and pH values (1), and a wide variety of intracellular and extracellular proteins has been identified with iso-Asp modifications. Iso-Asp formation is prevalent in stressed (heat shock) or aged cells (2), and the presence of iso-Asp residues in proteins has been shown to decrease biological functions in some proteins (3).…”
Section: T Cells Not Only Recognized the Isoaspartyl Trp-2 Peptide Bumentioning
confidence: 99%
“…Iso-Asp formation is prevalent in stressed (heat shock) or aged cells (2), and the presence of iso-Asp residues in proteins has been shown to decrease biological functions in some proteins (3). Iso-Asp residues can be repaired by the ubiquitous enzyme protein carboxyl methyltransferase (4).…”
Section: T Cells Not Only Recognized the Isoaspartyl Trp-2 Peptide Bumentioning
confidence: 99%